The Impact of Social Media Addiction on Adolescent Mental Health in Ambon City, Indonesia - Noya, Josephus; Lameky, Vernando Yanry (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The increasing prevalence of social media use among adolescents has raised concerns regarding its potential impact on mental health. This study investigated the relationship between social media addiction and adolescent mental health in Ambon, Indonesia. A quantitative cross-sectional research design was utilized, involving 336 adolescents aged 13-18 who actively used social media. Data were gathered through a structured questionnaire assessing demographic characteristics, social media usage patterns, and mental health status using the Depression Anxiety Stress Scale (DASS-21). Descriptive analysis, bivariate analysis using odds ratios (ORs), and multivariate analysis via multiple logistic regression were conducted. Results indicated that 64.88% of respondents had poor mental health scores. Bivariate analysis revealed significant associations between age, study frequency, duration of social media use, and social media usage scores with mental health conditions (p<0.05). Multiple logistic regression identified that adolescents aged 18-20 years, those who studied infrequently, used social media for over three hours daily, and had high social media usage scores were at greater risk of poor mental health. These findings underscore the importance of collaborative efforts among stakeholders to design effective interventions and policies that foster responsible social media use and promote adolescent mental well-being in the digital era.